Present status of holothurian fisheries in mullaitivu coastal waters in north-east region of sri lanka - Veronika, K.; Edrisinghe, U.; Sivashanthini, K.; Athauda, A.R.S.B. (University of Jaffna, 2017)
Present study was carried out at the landing sites at Challai, Puthumattalan and Peppearippiddy in Mullaitivu coastal region of Sri Lanka from May to September 2015. A total of 3 sea cucumber species belong to family Holothuridae and Stichopodidae were identified. Bohadschia marmorata was common in the catches and found in all three landing sites.. Holothurians were harvested through SCUBA diving. Holothuria spinifera and Stichopus naso were dominant in catches at Challai landing site while B. marmorata was dominant at Puthumattalan landing site. During the study period, the estimated highest number of individuals in catches was recorded in June in the three landing centers, Challai (84328), Puthumattalan (73457) and Peppearippiddy (36371), while the number of fishing efforts were 12-17 boats/day, 10-12 boats/day and 6-10 boats/day in the respective three locations. Nevertheless, there was no significant difference between the landing sites and species except for S. naso (P<0.05). The highest catch per diver per day of 117.2 individuals was reported in Challai. The estimated total number of Holothurians caught in Challai, Puthumattalan and Peppearippiddy during the present study was 608341. Of these 295373 individuals were caught from Challai, 167485 were from Puthumattalan and 145483 were caught from Peppearippiddy area. The outcome of this study can be used to develop a sustainable and proper management plan in exploring the future prospects of Holothurian fishery in Mullaitivu district .
Keywords: Bohadschia marmorata; Fishery dependent survey; Holothurians; SCUBA diving